Desarrollo de la competencia auditiva. Propuesta metodológica. (2011)
It is necessary to seek new ways to motivate teachers and students to make the ear training hearing into audition and improvisation games, developing in this way the listening competition. It establishes the difference between hearing and listening and presents a few steps necessary for this purpose.  First we make a warm-up, then a workout and finally we arrive at the listening competition  Thinking, intelligence and musical memory, are essential for the formation of the musical ear. You must pass from improvisation to oral dictation, then audiovisual recognition to finally proceed to take written dictation.  Writing develops the audiation when physical sound is not present, this way the conscious listening is refined represented by musical thought, meaning sound images, ¿how a major chord sounds?, ¿what is a perfect fifth-sounding melody or harmony?; audition converts hearing into listening. FABERMANA[2] methodology is the new proposal, thanks to the classroom in academic spaces for ";theoretical-auditive training and ear training";. There are currently some music education schools that are testing the methodology with significant success.[2] FABERMANA: methodological proposal from FABIO E. MARTINEZ NAVAS .